2019
DOI: 10.11591/ijai.v8.i1.pp77-86
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Hybrid Feature Selection Method for Huge Dimensional Datasets

Abstract: <span>Variable Selection is the most essential function in predictive analytics, that reduces the dimensionality, without losing an appropriate information by selecting a few significant features of machine learning problems. The major techniques involved in this process are filter and wrapper methodologies. While filters measure the weight of features based on the attribute weighting criterion, the wrapper approach computes the competence of the variable selection algorithms. The wrapper approach is ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Further, this study select corporate governance regime periods as features. It has been widely accepted that corporate governance mechanism enhance best practice in the form of corporate performance [22] and transparency [8]. The effective governance system can reduce tax avoidance as the system has the ability to govern and monitor corporate tax decisions [13].…”
Section: Research Methods 31 Dataset and Features Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, this study select corporate governance regime periods as features. It has been widely accepted that corporate governance mechanism enhance best practice in the form of corporate performance [22] and transparency [8]. The effective governance system can reduce tax avoidance as the system has the ability to govern and monitor corporate tax decisions [13].…”
Section: Research Methods 31 Dataset and Features Selectionmentioning
confidence: 99%
“…Motivated by the limitation, this paper attempts to fill the gap by developing model to predict tax avoidance strategies. In the recent Industrial 4.0 era, many recent studies have demonstrated that machine learning and big data mining approaches are effective tools for many problems [6][7][8][9][10] and also for the detection of financial fraud including tax fraud [11]. Despite the wiser used machine learning in many applications, there is limited literature on the development of related to tax avoidance.Therefore, this study has been initiated to fill the gap by looking at the experimental methods of developing tax avoidance classification model based on machine learning.…”
Section: Introductionmentioning
confidence: 99%
“…In ODP, metadata are published to describe the datasets under a specified standard format such as DCAT [21]. The portal uses the recommended DKAN framework to build the ODP [22]. The main page of the data portal does not contain any semantic vocabularies.…”
Section: Methodsmentioning
confidence: 99%
“…Audio Feature Extraction is a process done on the collected audio data. The features will allow recognition but high dimensional feaetures casues overfitting [20]. The Cepstral features such as MLE mimics the human preception of sound [21].…”
Section: Audio Feature Extractionmentioning
confidence: 99%